Effect of phytase supplementation of a plant-based diet on phosphorus and nitrogen bioavailability in sea bream Sparus aurata - Morales, Gabriel Alejandro (2014)
To assess to what extent addition of phytase to a plant-based diet results in spatio-temporal changes of phytate, available P, soluble protein, total amino acids and the activity of the main digestive proteases in gilthead sea bream, fish were fed two plant-based diets with or without phytase. Stomach, proximal intestine and distal intestine contents were monitored for these parameters at 0, 1, 2, 4 and 6 h after feeding. A reduction (P < 0.0001) of the soluble P–IP6 in the stomach when phytase was added to the diet was observed. Within stomach, most of the total P–IP6 was precipitated (86%), possibly due to the low acidification capacity of the sea bream (pH > 4), but 57% of the dietary P–IP6 was dephosphorylated, suggesting that phytase could have the capacity to dephosphorylate insoluble IP6 at such pH. An increment (60%) (P < 0.01) in total gastric protease activity was observed by phytase addition, this being the first demonstration of the in vivo effect of IP6 on the pepsin activity in fish stomach. Gastric pH and residence time of the digesta inside the stomach are critical factors for an efficient phytase action and improve P and N bioavailability in plant-based diets used in fish aquaculture.